2020
DOI: 10.1109/access.2020.3001753
|View full text |Cite
|
Sign up to set email alerts
|

Two-Echelon Vehicle-Routing Problem: Optimization of Autonomous Delivery Vehicle-Assisted E-Grocery Distribution

Abstract: The last mile problem of E-grocery Distribution comprises one of the most costly and highest polluting components of the supply chain in which companies deliver goods to end customers. To reduce transport cost and fuel emissions, a new element of ground-based delivery services, autonomous delivery vehicles (ADVs), is included in the E-grocery distribution system for improving delivery efficiency. Thus, the objective of this study is to optimize a two-echelon distribution network for efficient E-grocery deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…First, customers were assigned to the micro hubs based on the distance and loads of the customers. The clustered nodes were then assigned vehicles and routes were constructed by connecting the nodes ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, customers were assigned to the micro hubs based on the distance and loads of the customers. The clustered nodes were then assigned vehicles and routes were constructed by connecting the nodes ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…2E-VRP was initially proposed by Gonzalez-Feliu ( 16 ), and their newly published outcomes in Perboli et al ( 17 ) showed that 2E-VRP can be used to model delivery system involving a micro hub. The 2E-VRP is attributed to a VRP of two-echelon delivery connected by micro hubs ( 18 ) with unitary mode vehicles or mixed vehicles. For example, vans and cargo bikes ( 19 ), cargo bikes, and parcel lockers ( 20 ) are integrated into a two-echelon system to achieve a sustainable delivery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zamar et al [59] studied the bale collection optimization and designed a nearest neighbor approach together with a constrained k-means clustering to achieve the minimization of the fuel consumption and travel time simultaneously. Liu et al [60] proposed a two-step clustering-based hybrid algorithm to solve the two-echelon VRP with mixed vehicles and substantially minimized the transport cost and fuel emissions of the logistics network. Gao et al [61] developed a hybrid algorithm composed of k-means clustering and ant colony algorithm and introduced k-means clustering for handling the location allocation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fan et al [44] introduced a clustering algorithm based on the temporal-spatial distance to reduce the computational complexity and enhance the quality of initial solution in MDVRPTW. Liu et al [45] investigated the clustering algorithm that groups customers in terms of the minimum distance and maximum demand to improve the efficiency of solving MDVRPTW.…”
Section: Literature Reviewmentioning
confidence: 99%